Temporal trends in the prevalence of GP registrars’ long-term paediatric asthma control medications prescription - Nina Reid; Katie Fisher; Anna Ralston; Amanda Tapley; Elizabeth Holliday; Ian Charlton; Katherine Chen; Jason Dizon; Dominica Moad; Alison Fielding; Andrew Davey; Mieke van Driel; et al. (npj Primary Care Respiratory Medicine, 2024)
Abstract Asthma is one of the most common chronic illnesses affecting children. Long-term asthma control medications (LTACMs) are an important aspect of asthma management, with under-prescription associated with poor asthma control and increased asthma deaths. This study aimed to document temporal trends in the prescribing of LTACMs for paediatric patients for asthma-related presentations to Australian general practice registrars (trainees). Longitudinal analyses of data from 2010 to 2022 from the Registrars Clinical Encounters in Training study were undertaken. Proportions of paediatric presentations where LTACMs were prescribed were calculated, and temporal trends analysed and graphed. There was no change over time in registrar prescribing of LTACMs for paediatric asthma, although temporal changes were seen in the types of LTACMs prescribed. The lack of temporal increase in overall LTACMs prescription, despite evidence showing their importance in preventing asthma morbidity and mortality, has significant educational, clinical, and policy implications.